Fluorescent proteins and genetically encoded biosensors. (25th January 2023) - Wang, Minji; Da, Yifan; Tian, Yang
Abstract : The review summarises fluorescent proteins from natural sources, the design of biosensors with fluorescent proteins, and several typical types of genetically encoded fluorescent biosensors. Abstract : The genetically encoded fluorescent sensors convert chemical and physical signals into light. They are powerful tools for the visualisation of physiological processes in living cells and freely moving animals. The fluorescent protein is the reporter module of a genetically encoded biosensor. In this study, we first review the history of the fluorescent protein in full emission spectra on a structural basis. Then, we discuss the design of the genetically encoded biosensor. Finally, we briefly review several major types of genetically encoded biosensors that are currently widely used based on their design and molecular targets, which may be useful for the future design of fluorescent biosensors.